EMPLOYABILITY AND SOCIAL SCIENCE EDUCATION: A SOCIOLOGICAL ANALYSIS - R, Sugureshwar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Like many other nations of the world, India too has a huge reservoir of youth power, much of them residing in urban areas, either born there to parents migrated a few generations ago, or themselves moved to mega cities to seek quality education and vocational skills. India Skill Report 2016 has emphasized upon tackling the challenge of employability of the qualified youth and has recommended to the Government several new initiatives and policies to give a facelift to the country’s educational system. The chief variables here are Curriculum, Pedagogy, and Institutional Infrastructure. This paper aims to sociologically investigate into the situation with social science education and the challenges inherent in career building. It is based on an explorative study undertaken in Kalaburagi city covering some of its social science educational institutions, both undergraduate and post-graduate. The study has shown that there is a huge rural-urban and class divide between students successfully achieving higher standards of learning and in obtaining employment. The role of the family/parents and changing market value of social science subjects present a complex scenario.